ECONOMIC AND LEGAL ASPECTS OF SUNFLOWER INSURANCE USING THE MODEL OF REGIONAL INDEX - Marković, Todor; Veselinović, Janko; Kokot, Željko (Economics of Agriculture, 2018)
The application of index insurance in agriculture is becoming more and more popular in the last few years, especially in developed countries. Index insurance of crops and fruits is based on data related to a particular administrative unit or region. The regional index represents the average yield or average revenue in a region that is the basis for calculating the premium and insurance compensation. In the case of sunflower production, one of the most frequent crops in the region of Kula municipality, the authors show the methodology of applying the analysed insurance. The main advantage of this insurance model can be the facts that there is no need to estimate the damage, as well as a drastic reduction in morale-hazard. This insurance model can be a significant alternative to classical insurance and its implementation should result in an increase in the number of insured and insured areas. Firstly, it is necessary to remove the potential legal dilemmas about the implementation of this insurance model in Serbia and to define more precisely some legal institutions in this area.